The MArx-Engels Reader - Tucker, Robert C.. (New York W. W. Norton and Company, 1978)
This revised and enlarged edition of the leading anthology provides the essential writings of Marx and Engels those works necessary for an introduction to Marxist thought and ideology. Among the major features of the revision are selections from the " Contribution to the Critique of Hegel`s Philosophy of Right".
Keywords: History